A New "Special Relationship"?: Power Transitions, Ontological Security, and India–US Relations. Issue 3 (15th July 2013) - Chacko, Priya
Abstract : This article argues that power transitions generate not just physical security concerns for states, but also "ontological" insecurity, as established identities, hierarchies, and relationships are revised and challenged. It is suggested that seeking out "special relationships" with others is one way in which states seek to mitigate this uncertainty. Through an analysis of the discourse on the "rise of India" from policymakers and commentators in the United States, it is shown that recent US representations of India seek to consolidate a particular US identity, based on the notion of American exceptionalism, and attempt to construct a new "special relationship" with India in order to ameliorate the challenge posed by the rise of China to a US‐dominated world order and the assumption of the universality of US ideas and institutions. However, while India–US relations have improved, the relationship continues to be hampered by their differing world‐views and self‐perceptions, which, as in the past, undermine each other's sense of ontological security.